Konstruksi RUU PKS Dalam Framing Pemberitaan Media Online - Zakiya Fatihatur Rohma (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
The draft law of P-KS that has entered the hearing stage still raises polemic in the community. Basically, every new law will cause pros and cons. However, due to the pros and cons of the RUU P-KS in the community, there is a central role of the mass media. Through framing (news frame) media has the power to influence the perceptions of audiences. Therefore, this study aims to determine the construction of the RUU P-KS in framing online media coverage. The framing analysis used was the analysis of William A. Gamson and Modigliani's Framing. The online media analyzed are Voa-islam.com and Nu.or.id. The results showed that there were three images constructed by Voa-islam.com on the RUU P-KS, namely a good image of the PKS and Gerindra parties, a good image of the Islamic system and images of phrases of sexual violence. Whereas Nu.or.id also built three images on the framing of the RUU P-KS, namely the image of the importance of the RUU P-KS to be ratified, the image of both the DPR and the government and the image of the RUU P-KS is not a law that is pro-zina or LGBT